Penerapan model pembelajaran quick on the draw untuk meningkatkan minat dan hasil belajar siswa - Sari, Merita; Rahmatina, Desi; Izzati, Nur (Jurnal Pendidik Indonesia, 2025)
Teacher-centered instruction often results in low student interest and learning outcomes. This study aims to enhance students’ learning interest and achievement through the implementation of the Quick on the Draw (QOTD) learning model in mathematics lessons for eighth-grade students at SMP Integrasi As-Sunniyah. The study employed a collaborative classroom action research design conducted in two cycles, each consisting of two learning sessions and one achievement test. Data were collected through observation, learning interest questionnaires, and learning achievement tests. The findings revealed significant improvements in all observed aspects. Teacher activity increased from 64.28% to 92.85%, while student activity rose from 50% to 92.85%. Students’ learning interest improved from 72.20% in the first cycle to 87.36% in the second, and learning achievement increased from 41.17% to 88.23%. The implementation of the Quick on the Draw model effectively fostered an active, collaborative, and enjoyable learning atmosphere, enhancing both conceptual understanding and students’ motivation in mathematics.